Effect of recycled aggregate and freeze-thaw cycles on fatigue performance of asphalt concrete - Yan, Yihong; Li, Wenbo; Wang, Lei (Frontiers in Materials, 2025)
Fatigue damage is a primary mode of failure in asphalt pavements under repeated traffic loading. The incorporation of recycled concrete aggregate (RCA) in asphalt mixtures addresses issues of construction waste landfilling while enhancing sustainability. This study investigated the influence of RCA sizes and freeze-thaw (F-T) cycles on fatigue lives of recycled aggregate asphalt concrete (RAAC) through laboratory tests. Three RCA size fractions (4.75–9.5 mm, 9.5–13.2 mm, and 13.2–16 mm) underwent Los Angeles abrasion tests to quantify morphological changes, including convexity, axiality coefficient (AC), and roundness. After 800 abrasion rotations, fine RCA showed minimal convexity reduction of approximately 0.4%, whereas coarse RCA exhibited a greater reduction exceeding 1.0%. Semi-circular bend (SCB) fatigue tests revealed that RAAC specimens with finer RCA consistently exhibited better fatigue resistance and higher stiffness modulus retention compared to medium and coarse gradations. Grey correlation analysis indicated a strong correlation between RCA size and fatigue life, with AC identified as the most influential morphological index. Fatigue life predictions using Basquin model demonstrated high accuracy (R2 > 0.90). Furthermore, F-T cycles accelerated damage accumulation and stiffness reduction in RAAC over fatigue loading repetitions. These findings underscore the critical role of RCA particle morphology in enhancing RAAC durability under coupled environmental and mechanical loading conditions.